Oocyte Cryopreservation in Oncological Patients: Eighteen Years Experience of a Tertiary Care Referral Center - Specchia, Cristina; Baggiani, Annamaria; Immediata, Valentina; Ronchetti, Camilla; Cesana, Amalia; Smeraldi, Antonella; Scaravelli, Giulia; Levi-Setti, Paolo Emanuele (Frontiers in Endocrinology, 2019)
Objective: To report our experience on medical egg freezing for fertility preservation before cancer treatment. Design: This is a single-center retrospective observational study, including all patients who underwent e medical fertility preservation before oncological treatment between January 2001 and March 2019 at our Institute. Results: A total of 568 women received fertility counseling and 244 (42.9%) underwent 262 oocyte retrieval cycles after controlled ovarian stimulation for cryopreservation The majority of patients were diagnosed with breast cancer (59.8%), followed by women affected by Hodgkin’s and non-Hodgkin’s lymphoma (27.0%). A minority comprised patients diagnosed with other malignancies that affected soft tissues, sarcomas (2.9%), ovary borderline type (2.5%), digestive system (1.6%), leukemia (1.6%), uterine cervix (1.2%). The remaining 3.3% were affected by other cancer types. The mean age of the cohort was 31.3 ± 6.4 years and the mean oocyte retrieved was 13.5± 8.4. Of eleven women who returned to attempt a pregnancy, three performed two thawed cycles. We obtained 4 pregnancies (Pregnancy Rate 36.4% for couple): two miscarriages and two live births. Overall, 95.7% of oocytes are still in storage. Conclusions: A close collaboration between Cancer and Fertility Center in a tertiary care hospital is essential to provide a good health service in oncological patients. Offering fertility preservation is no longer considered optional and must be included in every therapeutic program for women who receive an oncological diagnosis in their reproductive age. Oocyte cryopreservation is a good option for fertility preservation for women facing cancer treatment and our results, despite on a small sample, are encouraging. We also confirm a low utilization rate as only 4.5% of patients returned to use their gametes.